ANÁLISE DA MANOBRA DE COMPRESSÃO-DESCOMPRESSÃO NO VOLUME CORRENTE DE PACIENTES SOB VENTILAÇÃO MECÂNICA - Fabiani Bertini Paes; Luiz Carlos de Abreu; Vitor Engracia Valenti; Marcelle Guerra; Claudio Leone; Rodrigo Daminello Raimundo (UniEVANGÉLICA, 2015)
Objective: To evaluate the change in tidal volume and hemodynamic variables after a mechanical compression-decompression maneuver in patients on ventilation Method: 32 patients under mechanical ventilation, with a mean age of 43 ± 18 years. The variables of systolic blood pressure were taken, diastolic blood pressure, Mean Arterial Pressure, Heart Rate, Oxygen Saturation and Tidal Volume in the moments before (M1), immediately after (M2) and after 10 minutes (M3) the application of the Protocol, consisting of 10 repetitions of compression-decompression maneuver in each patient. Results: A significant difference was found to the Tidal Volume of variables, mean that increased in M1 of 596 ± 126ml to the M2 648 ± 110ml and decreased in M3 to 607 ± 12 ml (p <0.001); Systolic blood pressure, which increased in M1 of 127 ± 19mmHg for the M2 of 141 ± 18 mmHg and decreased in M3 to 124 ± 16 mm Hg (p = 0.008) and heart rate, which increased in M1 81 ± 14 bpm to M2 96 ± 18bpm and decreased again to 87 ± 16bpm M3 (p <0.001). Conclusion: The maneuver compression-decompression in patients under mechanical ventilation, tidal volume increases significantly in the immediate moment after application, and this increase is not maintained after 10 minutes.